The Next 10 Years in Voice Evaluation and Treatment - Barkmeier-Kraemer, Julie M.; Patel, Rita R. (Seminars in Speech and Language, 2016)
Voice disorders are thought to affect approximately one third of all individuals within the United States during their lifetime. Individuals who require the use of their voice as part of their occupations are at highest risk for developing voice problems. Unfortunately, efficient diagnosis and effective management of voice disorders can be challenged by difficulty accessing professionals with the necessary expertise to diagnose and treat voice problems efficiently. Within the next decade, technological advancements show promise for improving the efficiency and effectiveness of intervention for voice disorders. Exciting developments in laryngeal imaging, modeling of patient-specific vocal patterns, and implementation of smart mobile technology and telehealth will greatly improve the accuracy of diagnosing voice problems and enhance implementation and carryover of effective voice treatment methods to daily communication demands.
Keywords: Voice; voice disorders; evaluation; treatment; technology